The atmospheric transport of iodine‐129 from Fukushima to British Columbia, Canada and its deposition and transport into groundwater. Issue 12 (17th December 2015) - Herod, Matt N.; Suchy, Martin; Cornett, R. Jack; Kieser, W. E.; Clark, Ian D.; Graham, Gwyn
Abstract: The Fukushima‐Daiichi nuclear accident (FDNA) released iodine‐129 (15.7 million year half‐life) and other fission product radionuclides into the environment in the spring and summer of 2011. 129 I is recognized as a useful tracer for the short‐lived radiohazard 131 I, which has a mobile geochemical behavior with potential to contaminate water resources. To trace 129 I released by the FDNA reaching Canada, pre‐accident and post‐accident rain samples collected in Vancouver, on Saturna Island and from the National Atmospheric Deposition Program in Washington State were measured. Groundwater from the Abbotsford‐Sumas Aquifer was sampled to determine the fate of 129 I that infiltrates below the root zone. Modeling of vadose zone transport was performed to constrain the travel time and retardation of 129 I. The mean pre‐accident 129 I concentration in rain was 31 × 10 6 atoms/L (n = 4). Immediately following the FDNA, 129 I values increased to 211 × 10 6 atoms/L and quickly returned to near‐background levels. However, pulses of elevated 129 I continued for several months. The increases in 129 I concentrations from both Vancouver and Saturna Island were synchronized, and occurred directly after the initial release from the FDNA. The 129 I in shallow ( 3 H/ 3 He age <1.4 years) Wassenaar et al. (2006) groundwater showed measurable variability through March 2013 with an average of 3.2 × 10 6 atoms/L (n = 32) that was coincident with modeled travel times for Fukushima 129 I. The groundwater response and the modeling results suggest that 129 I was partially attenuated in soil, which is consistent with its geochemical behavior; however, we conclude that the measured variability may be due to Fukushima 129 I entering groundwater. Key Points: 129 I fallout was measured in Vancouver after the Fukushima‐Daiichi nuclear accident A 129 I pulse was identified in precipitation and potentially in local groundwater Vadose zone modeling constrained adsorption and transport of 129 I into groundwater